Homo Sapiens Socialis - Alexander Subbotin (Journal of Economic Sociology, 2020)
Homo sapiens is the greatest mystery of science. The main property of this biological species is the mind, but what are the laws of consciousness and how does ignorance of these laws hinder the development of ideas about various spheres of functioning of society? These and other relevant issues of cognitive science are tackled in the book Minds Make Societies: How Cognition Explains the World Humans Create by Pascal Boyer, a professor at the University of Washington. This work is reviewed so that potential readers can understand how convincing the author is in solving the tasks he sets—the problems of a new science, the foundations of which he intends to lay. The French-American evolutionary psychologist poses six questions: What is the basis of intergroup conflicts? Why do we need information? Why do religions exist? What is natural family? How can society be fair? Can our minds comprehend society? In answering these questions, Boyer uses a variety of facts from various disciplines of natural science and humanities. The scholar seeks to show and refute the prejudices of many prevailing concepts, for example, the traditional opposition between nature and culture, which has dominated for several centuries. The anthropologist provides a lot of fascinating data, including from personal field experience, and does so using simple language. However, in the end, most hypotheses are explained by human evolution and the need for groups to simultaneously consolidate within themselves and resist other communities. The book could be useful to anyone interested in anthropology and the structure of society, as well as laws of thought.